Modulation of the cytoplasmic functions of mammalian post-transcriptional regulatory proteins by methylation and acetylation: a key layer of regulation waiting to be uncovered?. (27th November 2015) - Blee, Tajekesa K.P.; Gray, Nicola K.; Brook, Matthew
Abstract : Post-transcriptional control of gene expression is critical for normal cellular function and viability and many of the proteins that mediate post-transcriptional control are themselves subject to regulation by post-translational modification (PTM), e.g. phosphorylation. However, proteome-wide studies are revealing new complexities in the PTM status of mammalian proteins, in particular large numbers of novel methylated and acetylated residues are being identified. Here we review studied examples of methylation/acetylation-dependent regulation of post-transcriptional regulatory protein (PTRP) function and present collated PTM data that points to the huge potential for regulation of mRNA fate by these PTMs.